Public Opinion about International Trade: assessing the impact of cultural proximity - Giwa, Gillian Travia (2014)
The use of experimental methods in International Relations (I.R.) studies continues to be relatively unpopular, and especially so among the International Political Economy (IPE) research fraternity in Brazil. Notwithstanding, this paper is the product of an experimental survey administered among the undergraduate students\' population at the University of São Paulo in April 2014, in which the hypothesis that cultural proximity mattered to public opinion about trade partners was investigated and subsequently validated. In pretreatment tests, language, religion and social norms and values were identified as proxies for cultural proximity. These were incorporated into four treatment vignettes that described a potential trade partnership in terms of its economic gains as well as the cultural (dis)similarity of the partner country. With the addition of a control condition - having no economic or cultural information - the five vignettes were embedded into questionnaires administered to 503 students across 7 faculties. Treatment effects under all conditions confirmed that people\'s decisions were affected by the cultural indicators. Their contradictory response to descriptive questions however, implies that though their actions may be conducive with culturally influence, people\'s declarations will tend to suggest otherwise.